(untitled) (Journal of Asian Development Studies, 2025)
In today’s technological age, millions of students worldwide play Clash of Clans. This study aimed to examine the impact of Clash of Clans addiction on aggression, with a focus on the mediating role of emotional regulation. A sample of 250 Clash of Clans addicts, with an equal gender distribution (males = 125, females = 125), was selected for the study. The instruments used to assess the study variables were the Gaming Addiction Scale for Adolescents, the Buss and Perry Aggression Questionnaire, and the Emotional Regulation Questionnaire. Participants were aged between 18 and 25 years (M = 20.65, SD = 2.37). The findings revealed a significant positive mediating effect of expressive suppression between Clash of Clans addiction and aggression, while cognitive reappraisal negatively mediated the relationship. The study provided several implications for the well-being of young adults, including government action, awareness by mental health professionals, positive parental involvement with children, and promoting help-seeking behavior among young adults in Pakistan. The results were discussed in the context of existing literature, and recommendations for future research were provided.